SIBALI PARRIQ: REPRESENTATION OF LOCAL CULTURAL VALUES IN GENDER EQUALITY IN MANDAR SOCIETY (International Conference on Social and Islamic Studies, 2022)
When entering life in marriage, men will have a new role, namely as a husband, while women will also have a new role in their household life as a wife. In addition, if men and women already have children, they will also play the role of father and mother. In society, a husband will be tasked with earning a living, in this study as a fisherman or farmer, but they also help their wife in taking care of the household, and take care their children, the wife does not only taking care of the household or take care their children, but also helps her husband in earn a living. The fish or garden’s produce will be sell by the wife, while the husbands taking care of the household, including taking care of their children. In this paper, we will focus on the concept of Sibaliparriq which is carried out by married couples who work together and help each other to create harmonious family conditions. In this study we used a qualitative approach and used in-depth interviews and observation as data collection methods. There were 7 people who became informants in this study and the informants differed by age and occupation. This study explains that there is the concept of Sibaliparriq in the division of roles in household affairs between husband and wife and also work hand in hand for the welfare of the family. The Sibaliparriq concept can be carried out well by husband and wife because there is a balanced division of roles carried out by both husband and wife which is also accompanied by mutual support and also mutual understanding so that each of them is able to carry out their respective roles properly.